Two Chalcone Synthase Isozymes Participate Redundantly in UV-Induced Sakuranetin Synthesis in Rice - Hye Lin Park (International Journal of Molecular Sciences, 2020)
: Chalcone synthase (CHS) is a key enzyme in the flavonoid pathway, participating in the production of phenolic phytoalexins. The rice genome contains 31 CHS family genes (OsCHSs). The molecular characterization of OsCHSs suggests that OsCHS8 and OsCHS24 belong in the bona fide CHSs, while the other members are categorized in the non-CHS group of type III polyketide synthases (PKSs). Biochemical analyses of recombinant OsCHSs also showed that OsCHS24 and OsCHS8 catalyze the formation of naringenin chalcone from p-coumaroyl-CoA and malonyl-CoA, while the other OsCHSs had no detectable CHS activity. OsCHS24 is kinetically more efficient than OsCHS8. Of the OsCHSs, OsCHS24 also showed the highest expression levels in different tissues and developmental stages, suggesting that it is the major CHS isoform in rice. In oschs24 mutant leaves, sakuranetin content decreased to 64.6% and 80.2% of those in wild-type leaves at 2 and 4 days after UV irradiation, respectively, even though OsCHS24 expression was mostly suppressed. Instead, the OsCHS8 expression was markedly increased in the oschs24 mutant under UV stress conditions compared to that in the wild-type, which likely supports the UV-induced production of sakuranetin in oschs24. These results suggest that OsCHS24 acts as the main CHS isozyme and OsCHS8 redundantly contributes to the UV-induced production of sakuranetin in rice leaves.